Qualitative Factors that Influence Tourism Interests Visiting Tourism Destinations in Indonesia - Pramono, Teguh (Global Journal of Social Sciences Studies, 2019)
This study aims to describe the qualitative factors that influence domestic tourists visiting tourist destinations. This research uses a qualitative approach. The tourist destinations that became the location of the study were the spiritual tourism destination of Maria Lounders Cave, PohSarang Village, Kacamatan Semen, Kediri Regency, East Java and the Tomb of WaliSongoSunanAmpel in Surabaya, East Java, Indonesia. Primary data was collected using participatory observation techniques, in-depth interviews, and documentation. Data were analyzed using four steps of qualitative research, including data collection, data filtering, data classification, and drawing conclusions. Based on the results of the study it can be concluded that, the factors that affect the interest of tourists visiting tourist destinations are: the completeness of facilities and infrastructure, tourist image, service, attraction, comfort, promotion, and tourist preferences. Based on interview results, those qualitative variables are always sought after by tourists. They want to visit a destination because of its promotion, attractiveness, and good image. Service, comfort, and tourist preferences are also reasons why these tourists visit tourist destinations.